Evaluasi Hasil Persilangan Ayam Lurik, Ayam Merawang dan Ayam Komering 267 Evaluasi Hasil Persilangan Ayam Lurik, Ayam Merawang dan Ayam Komering - Depison, Depison (Fakultas Peternakan Universitas Jambi, 2006)
This research was aimed to study the breeding result between Lurik chicken versus Merawang and Komering chicken and between Merawang and Komering chicken.. Experimental variables were taken in this research were egg production, egg weight, fertility, hatched weight, daily weight gain, feed efficiency, chicken feather colour, comb shape, leg colour, skin and meat colour. Evaluated data was observed from the breeding of Lurik, Merawang and Komering chickens, progeny of Lurik versus Merawang, progeny of Lurik versus Komering and progeny of Komering versus Merawang. Observed data was analysed by addition, persentage and deviasi standard (X ± sd) (Steel dan Torrie, 1993). T test was used to compare egg production, egg weight, fertility, hatched weight, daily weight gainand feed efficiency among the breeding treatments using Siegel instruction (1994). Based on the research, it could be concluded : 1) egg weight and hatched weight of merawang were better than Lurik, Komering, progeny of Lurik versus Merawang, Lurik versus Komering and Merawang versus Komering, 2) The Productivity of breed of Lurik versus Merawang was higher than the breed of Lurik versus Komering and Merawang versus Komering. 3) The breed of Komering versus Lurik was not signifivantly different in increasing of egg production and decreasing of feed conversion. 4) There was no difference of feed comsumption between Merawang, Komering and progenys of Merawang and Komering versus Lurik.